2017
DOI: 10.1016/j.neuropsychologia.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling stimulus plausibility and contextual congruency: Electro-physiological evidence for differential cognitive dynamics

Abstract: A B S T R A C TExpectancy mechanisms are routinely used by the cognitive system in stimulus processing and in anticipation of appropriate responses. Electrophysiology research has documented negative shifts of brain activity when expectancies are violated within a local stimulus context (e.g., reading an implausible word in a sentence) or more globally between consecutive stimuli (e.g., a narrative of images with an incongruent end). In this EEG study, we examine the interaction between expectancies operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
(110 reference statements)
3
8
0
Order By: Relevance
“…In EEG, incongruent word(s)-picture pairs triggered an N400 effect in both unmasked sentence and single word trials. This is in line with previous work, showing that manipulating semantic congruency within word-picture pairs elicits N400 effects (Coco et al, 2017;Federmeier and Kutas, 2001;Willems et al, 2008). On the contrary, in the masked condition, an N400 effect was only observed for single words and not for sentences.…”
Section: Figure N400 Erp Effect Of Experiments 2 (A)supporting
confidence: 93%
“…In EEG, incongruent word(s)-picture pairs triggered an N400 effect in both unmasked sentence and single word trials. This is in line with previous work, showing that manipulating semantic congruency within word-picture pairs elicits N400 effects (Coco et al, 2017;Federmeier and Kutas, 2001;Willems et al, 2008). On the contrary, in the masked condition, an N400 effect was only observed for single words and not for sentences.…”
Section: Figure N400 Erp Effect Of Experiments 2 (A)supporting
confidence: 93%
“…Indeed, while we here focused on wordless visual narratives, image sequences typically appear in multimodal relationships, such as combined with written language. ERP research has shown that visual narratives integrated with text (Manfredi et al., ) and paired with auditory speech/sounds (Manfredi, Cohn, De Araújo Andreoli, & Boggio, ) elicit N400s and late effects with the same time course as in unimodal contexts, consistent with other studies of crossmodal and multimodal processing (Coco, Araujo, & Petersson, ; Liu, Wang, & Jin, ; Liu, Wang, Wu, & Meng, ; Weissman & Tanner, ; Wu & Coulson, ). Such findings support that the N400 reflects semantic activation that is only semisensitive to modality‐specific inputs (as suggested by variance in the scalp distribution of the N400 to different modalities).…”
Section: Further Implicationssupporting
confidence: 78%
“…The corresponding FRP waveforms showed a negative shift over frontal and central scalp sites when participants fixated a scene-inconsistent object. This result is in agreement with traditional ERP studies that have shown an frontocentral N300/N400 complex after passive foveal stimulation (e.g., Coco et al, 2017;Ganis & Kutas, 2003;Mudrik et al, 2014;Võ & Wolfe, 2013) and extends this finding for the first time to a natural viewing situation with eye-movements. Importantly, the time course of this effect suggests that it was already initiated during the preceding fixation (t-1), but then carried on through fixation (t) on the target object.…”
Section: Discussionsupporting
confidence: 92%
“…This long-lasting negative shift typically starts as early as 200-250 ms after stimulus onset (Mudrik, Shalgi, Lamy, & Deouell, 2014;Draschkow, Heikel, Võ, Fiebach, & Sassenhagen, 2018) and has its maximum at frontocentral scalp sites, in contrast to the centroparietal N400 effect for words (e.g., Kutas & Federmeier, 2011). The effect was found when the object appeared at a cued location after the scene background was already shown (Ganis & Kutas, 2003), for objects that were photoshopped into the scene (Mudrik, Lamy, & Deouell, 2010;Mudrik, et al, 2014;Coco, Araujo, & Petersson, 2017), and for objects that were part of realistic photographs (Võ & Wolfe, 2013). ERP effects of object-scene consistency have typically been subdivided into two distinct components: N300 and N400.…”
Section: Introductionmentioning
confidence: 95%